Effect of Microwave Curing on the Performance of High-volume Fly Ash Concrete - Lam, Tri-Khang; Nguyen, Dinh-Thang; Le, Tri Ho Minh; Huynh, Trong-Phuoc (Periodica Polytechnica Civil Engineering, 2024)
Concrete curing significantly impacts mechanical properties and durability, yet traditional methods face efficiency challenges. Microwave curing (MC) offers a promising alternative, providing rapid and uniform concrete curing. However, fully understanding the impact of MC on concrete performance, particularly in high-volume fly ash concrete (HVFC), remains a research gap. This study addresses this gap by investigating the effect of MC on key properties of HVFC, including compressive strength, drying shrinkage, chloride ion penetration, and resistance to sulfate attack. Concrete specimens underwent MC at varied energies (200–1000 W) and durations (10–30 min) to evaluate their mechanical and durability characteristics. Results show that MC significantly boosts early-stage concrete strength, notably at high applied energy. The specimen cured at 1000 W for 30 min (MC1000-30) achieved the highest 1-day strength of 23.68 MPa. However, the normal curing specimen exhibited the highest strength of 32.07 MPa at 28 days while the strength value of the MC1000-30 specimen declined to 20.25 MPa, indicating a 36.85% decrease. Although declining strength was observed after 28 days, the MC1000-30 specimen demonstrated improved durability with significantly reduced drying shrinkage (by 83.12%) and chloride ion penetration (by 31.6%). The study underscores the feasibility of utilizing MC for HVFC as it demonstrated significant enhancements in both early-stage concrete strength and durability at a later stage. Careful parameter optimization can ensure sustained effectiveness over time, offering a viable alternative to traditional curing methods.